Fibrous polymer nanomaterials for biomedical applications and their transport by fluids: an overview. Issue 42 (19th October 2018) - Pawłowska, S.; Kowalewski, T. A.; Pierini, F.
Abstract : Development and rheological property evaluation of fibrous polymer nanomaterials for novel biomedical applications related to material targeting: a review. Abstract : Over the past few decades, there has been strong interest in the development of new micro- and nanomaterials for biomedical applications. Their use in the form of capsules, particles or filaments suspended in body fluids is associated with conformational changes and hydrodynamic interactions responsible for their transport. The dynamics of fibres or other long objects in Poiseuille flow is one of the fundamental problems in a variety of biomedical contexts, such as mobility of proteins, dynamics of DNA or other biological polymers, cell movement, tissue engineering, and drug delivery. In this review, we discuss several important applications of micro and nanoobjects in this field and try to understand the problems of their transport in flow resulting from material-environment interactions in typical, crowded, and complex biological fluids. Our aim is to elucidate the relationship between the nano- and microscopic structures of elongated polymer particles and their flow properties, thus opening the possibility to design nanoobjects that can be efficiently transported by body fluids for targeted drug release or local tissue regeneration.